INTERPERSONAL COMMUNICATION STRATEGY FOR PRISON OFFICERS IN DEVELOPING PRISONERS IN CLASS IIA COMMUNITY INSTITUTIONS SERANG - Silalahi, Dhini Annissa; Soge, Markus Marselinus (PT Altin Riset Publishing, 2024)
Prisoners are also social creatures who will need others to interact continuously. The interaction will involve communication, and the importance of communication in the application of interpersonal communication strategies to carry out coaching aimed at improving the behavior of prisoners in Serang Class IIA Prison. The problems examined in this study include observing the interpersonal communication strategies of prison officers in fostering prisoners and the obstacles that exist during its implementation. This research was conducted to find out the application of interpersonal communication strategies of Correctional Institution officers in fostering prisoners and to find out the obstacles to the application of interpersonal communication strategies at Class IIA Serang Correctional Institution. The method used is a qualitative method, which examines in depth with data collection techniques such as observation and interviews. This research uses the theory of interpersonal communication strategy which is a process of relationship with others. The results of his research apply strategies from the dimensions of positive attitudes, supportive attitudes, empathy, openness, and equality and their implementation is almost running well because the coaching carried out has followed existing procedures, although there are still things that happen in prisons such as inmate indiscipline, it can be resolved wisely with communication. In carrying out the coaching program, of course, Serang Class IIA Prison has inhibiting factors, namely barriers in the delivery process, psychosocial barriers, lack of transparency, and different language styles.